(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Recent guidelines adapted unique pregnancy thyroid function screening tests because pregnancy subclinical hypothyroidism is associated with different adverse outcomes. There are no data from Iraq about the prevalence of thyroid hypofunction in the 1st trimester of pregnancy. This study aims to find the prevalence of thyroid dysfunction in the 1st trimester. Patients and Methods: In this descriptive cross-sectional study, thyroid stimulating hormone (TSH) was measured in 100 pregnant women from May 2017-December 2017 in Babylon teaching hospital for maternity and pediatric and in private clinic. If TSH was more than 2.5 mIU/L in the first trimester, free T4 was measured to diagnose then differentiate between subclinical & overt hypothyroidism. If free T4 was in the normal value (0.7-1.8 ng/dl) the diagnosis was subclinical hypothyroidism and if below the normal value, overt hypothyroidism was diagnosed.